2022
DOI: 10.1007/s42976-022-00258-1
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin contamination of maize (Zea mays L.) samples in Hungary, 2012–2017

Abstract: Mycotoxin contamination of maize often raises risks for human and animal health. The most frequently detected mycotoxins in maize are trichothecenes, fumonisins, and aflatoxin. A total number of 17,011 maize samples were tested by SGS for their mycotoxin content between 2012 and 2017. The toxin results clearly show that the southern areas of the country had higher levels of toxin contamination than the average. According to the dataset, aflatoxin contamination has become regular but the appearance of fumonisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…When preharvest AFB1 is above 20 μg/kg, preventive methods with a higher resistance, supported by agronomy and other means, are crucial [ 13 , 14 ]. Toxin data from SGS Company [ 15 ] showed that DON, fumonisins, and AFB1 have been regular components of corn grains every year since 2012, with large local differences. As the data (except the low rates) originated from mixtures from different fields and hybrids [ 16 ], the data could not be connected to individual hybrids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When preharvest AFB1 is above 20 μg/kg, preventive methods with a higher resistance, supported by agronomy and other means, are crucial [ 13 , 14 ]. Toxin data from SGS Company [ 15 ] showed that DON, fumonisins, and AFB1 have been regular components of corn grains every year since 2012, with large local differences. As the data (except the low rates) originated from mixtures from different fields and hybrids [ 16 ], the data could not be connected to individual hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Magan et al [ 24 ] analyzed DON for wheat, fumonisins, and AFB1 in maize and found that increasing warmth and dryer weather will favor fumonisins and aflatoxins in maize, and warm temperatures with excessive rain will increase DON in wheat. This also applies to DON contamination in maize [ 15 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus strains were found in 63.5% of the examined samples, of which 18.8% were able to produce aflatoxin. In 2012 and 2017, aflatoxin-contaminated grain was also detected [ 34 ]. Virág et al [ 35 ] examined the presence of A. flavus and A. niger in the field between 2019–2020.…”
Section: Discussionmentioning
confidence: 99%
“…Masic et al [ 25 ] reported on maize samples from Hungary, but the status of the samples (preharvest or stored) was not provided. In Hungary, data on 17,011 maize samples regarding mycotoxins was published from 2012 to 2017 [ 26 ]. Aflatoxins were found every year, with maximums between 0.44 and 115 μg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins were found every year, with maximums between 0.44 and 115 μg/kg. As the data originated mostly from stored mixed corn samples, no conclusions could be drawn about the preharvest or postharvest origins of the contamination or the possible role of resistance [ 26 ]. Therefore, aflatoxin was included into the tested toxins.…”
Section: Introductionmentioning
confidence: 99%